Optimization of piezoelectric ultrasound emitter transducers for underwater communications - Martins, Marcos Silva (2012)
Ultrasound transducers are typically based on piezoelectric materials, due to their good response at high frequencies. Depending on the application, ceramics, polymers and composite materials can be used. In this work, an optimization study of ultrasound transducers for underwater communications is addressed, focusing on a piston type emitter transducer operating in thickness mode (d33). The piston is constituted by an active element disk with optimized dimensions. It is discussed how the acoustic impedance, thickness, resonance frequency and structure affect the transducer performance. This work allows a better understanding of the emitter transducer characteristics allowing reaching the optimum point of operation for specific applications. Focusing on underwater communication, the acoustic channel is defined and the transducer is optimized by finite element computer simulations. The results were compared with experimental tests, which show that four-layer structures increase up to 16 dB in performance versus single-layer.